Biomass Accumulation and Nutritional Requirements of Potato as Affected by Potassium Supply - Soratto, Rogério P. [UNESP]; Job, André L. G. [UNESP]; Fernandes, Adalton M. [UNESP]; Assunção, Natália S. [UNESP]; Fernandes, Fabiana M. [UNESP] (Springer Nature, 2020)
Potassium (K) supply affects the growth and tuber yield of potato (Solanum tuberosum L.) as well as the uptake and removal of certain nutrients. However, information on this is scarce or inconsistent. Thus, this study was undertaken to evaluate the dry matter (DM) accumulation and the uptake and removal of nutrients by potato ‘Agata’ as affected by K fertilizer management (rates and application timings) in tropical clay soils with varied K availability. In soils with low K availability, K fertilization increased (P ≤ 0.05) the biomass of potato plants without differences among management types; however, in soils with medium and high K availability, K fertilizer did not alter the plant DM accumulation. K fertilization increased (P ≤ 0.05) N, K, Ca, Mg, S, B, Mn, and Zn uptake and removal in the soil with low K availability, while in soils with medium and high K availability, K fertilization had less influence on the uptake and removal of nutrients, except that K uptake and removal increased (P ≤ 0.05) under K fertilization, evidencing luxury uptake. In the soil with medium K availability, K application reduced (P ≤ 0.05) Mg uptake by plants, but this effect was not observed in soils with high K availability. Mn uptake and removal increased (P ≤ 0.05) under K fertilization in soils with low and high K availability. The increases in the uptake and removal of almost all nutrients in response to K fertilization were related to the increase in plant DM accumulation, but changes in the concentrations of K and some other nutrients also contributed to their increased uptake and removal.
Keywords: K fertilizer; Mineral nutrition; Nutrient removal; Nutrient uptake; Solanum tuberosum; Split application